A Chromosome-Level Genome Assembly of the Parasitoid Wasp, Cotesia glomerata (Hymenoptera: Braconidae). (27th May 2021) - Pinto, Brendan J; Weis, Jerome J; Gamble, Tony; Ode, Paul J; Paul, Ryan; Zaspel, Jennifer M
Abstract: Hymenopterans make up about 20% of all animal species, but most are poorly known and lack high-quality genomic resources. One group of important, yet understudied hymenopterans are parasitoid wasps in the family Braconidae. Among this understudied group is the genus Cotesia, a clade of 1, 000 species routinely used in studies of physiology, ecology, biological control, and genetics. However, our ability to understand these organisms has been hindered by a lack of genomic resources. We helped bridge this gap by generating a high-quality genome assembly for the parasitoid wasp, Cotesia glomerata (Braconidae; Microgastrinae). We generated this assembly using multiple sequencing technologies, including Oxford Nanopore, whole-genome shotgun sequencing, and 3D chromatin contact information (HiC). Our assembly is one of the most contiguous, complete, and publicly available hymenopteran genomes, represented by 3, 355 scaffolds with a scaffold N50 of 28 Mb and a BUSCO score of 99%. Given the genome sizes found in closely related species, our genome assembly was 50% larger than expected, which was apparently induced by runaway amplification of 3 types of repetitive elements: simple repeats, long terminal repeats, and long interspersed nuclear elements. This assembly is another step forward for genomics across this hyperdiverse, yet understudied order of insects. The assembled genomic data and metadata files are publicly available via Figshare (https://doi.org/10.6084/m9.figshare.13010549 ).